Nitrogen contribution of five leguminous trees and shrubs to alley cropped maize - Okogun, J.; Sanginga, P.; Mulongoy, N. (2000)
There are abundant local legume trees and shrubs potentially suitable for alley cropping systems in the sub-Saharan Africa, which are yet to be studied. The nitrogen contribution of two years old Albizia lebbeck and S. corymbosato yield of maize grown in alley cropping was compared to that of Senna siamea, Gliricidia sepium and Leucaena leucocephala in four seasons at Ibadan. Maize shoot biomass and maize grain yield in A. lebbeck alley compared favourably with that in G. sepium and L. leucocephala. Maize biomass and grain yield in S. corymbosa alleys were the lowest. Within A. lebbeck, L. leucocpehala, and G. sepium alleys there were no significant differences in the maize yield in the alleys that received 0, 40 or 80 kg N/ha. Application of more than 40 kg N/ha in S. corymbosa alleys was not necessary as there was no significant increase in maize yield at the higher level of nitrogen. Maize yield and N uptake in A. lebbeck alleys were not significantly different from yield and N uptake in G. sepium, and L. leucocephala at the same fertilizer level. There was a significant correlation between hedgerow tree biomass and maize grain yield. At the end of twelve weeks after pruning application, the organic residues of the pruning applied in the alleys ranged from 5% in G. sepium and 44% in A. lebbeck in the first year compared with the original pruning applied which showed that the slow rate of A. lebbeck decomposition could have a beneficial effect on the soil. The maize N recovery from applied N fertilizer was low (10–22%). Percentage N recovery from the prunings was low in the non-N fixing trees (12–22%), while the recovery was high (49–59%) in A. lebbeck as well as in the other nitrogen fixing tree prunings. Thus A. lebbeck, apart from enhancing maize growth and grain yield like in L. leucocephala and G. sepium, had an added advantage because it remained longer as mulching material on the soil because of its slow rate of decomposition. It was able to survive pruning frequencies with no die-back. This indicates that A. lebbeck is a good potential candidate for alley cropping system in West Africa. S. corymbosa performed poorly compared with the other legume trees. Though it responded to N fertilizer showing a positive interaction between the hedgerow and fertilizer application, it had a high die back rate following pruning periods and termite attack.